Meta Analysis: Prevalence and Effect of Knowledge on Anemia in Adolescent Girls - Kalsum, Ummi; Diastanti, Yunita; Guspianto, Guspianto (Riset Informasi Kesehatan, 2025)
Background: The prevalence of anemia in adolescent girls is high globally and in Indonesia. Various factors, including low-level knowledge, play a role in the onset of anemia in adolescents. The purpose of this study was to analyze the results of studies on anemia knowledge in adolescent girls to obtain a combined effect. Method: This systematic review included a meta-analysis. The journal sources were Google Scholar, Pub-med, and Scopus, and the search was performed using Publish or Perish Software, applying keywords using Boolean operators. The inclusion criteria were Indonesian or English language articles, full text from 2013 to 2022, cross-sectional studies, adolescent female populations, and multiple logistic regression analyses with adjusted odds ratio measures. A total of 10,499 articles were identified, of which 6 articles met the inclusion criteria. Data analysis using RevMan 5.4. Results: The prevalence of anemia in adolescent girls was 40.2% (95% CI: 12.98-67.68). Meta-analysis showed that knowledge about anemia had an influence on the incidence of anemia in adolescent girls (SMD=3.06; CI 95%=2.23-4.19; P-value=<0.001). The fixed-effect model was used. The funnel plot indicates that there was no publication bias in this study. Conclusion: Poor knowledge increases the risk of developing anemia in adolescents. It is recommended to increase literacy through social media related to anemia in adolescent girls and to activate adolescent health programs in schools.